PENGARUH MOTIVASI KUALITAS, KARIR, EKONOMI, DAN BIAYA PENDIDIKAN PADA MINAT MAHASISWA MENGIKUTI PENDIDIKAN PROFESI AKUNTANSI - Aryani, Ni Putu Devi; Erawati, Ni Made Adi (E-Jurnal Akuntansi; Vol 16 No 1 (2016), 2016)
This study aims to determine the effect of motivation quality, career motivation, economic motivation, and the cost of education in the interest of students to follow Accounting Profession. The study sample consisted of 47 students PPAk Faculty of Economics and Business, University of Udayana. The data collection method used was a questionnaire distributed to all students PPAk force XXII and XXIII, Faculty of Economics and Business, University of Udayana. Analysis of the data in this study using multiple linear regression analysis to see the goodness of fit the statistical value F, t statistics, and the coefficient determination. Based on the analysis, that the motivation quality positive effect on student interest PPAk follow. Career motivation positive effect on the interests of students follow PPAk. Economic motivation positive effect on the interests of students follow PPAk. Education costs negatively affect the interest of students to follow PPAk
Keywords: Quality Motivation, Career Motivation, motivation Economics, Education Costs, Interest Following PPAk